Are new TiNbZr alloys potential substitutes of the Ti6Al4V alloy for dental applications? An electrochemical corrosion study - Roselino Ribeiro, Ana Lucia [UNESP]; Hammer, Peter [UNESP]; Vaz, Luis Geraldo [UNESP]; Rocha, Luis Augusto [UNESP] (Iop Publishing Ltd, 2013)
The main aim of this work was to assess the electrochemical behavior of new Ti35Nb5Zr and Ti35Nb10Zr alloys in artificial saliva at 37 degrees C to verify if they are indicated to be used as biomaterials in dentistry as alternatives to Ti6Al4V alloys in terms of corrosion protection efficiency of the material. Electrochemical impedance spectroscopy (EIS) experiments were carried out for different periods of time (0.5-216 h) in a three-electrode cell, where the working electrode (Ti alloys) was exposed to artificial saliva at 37 degrees C. The near-surface region of the alloys was investigated using x-ray photoelectron spectroscopy (XPS). All alloys exhibited an increase in corrosion potential with the immersion time, indicating the growth and stabilization of the passive film. Ti35Nb5Zr and Ti6Al4V alloys had their EIS results interpreted by a double-layer circuit, while the Ti35Nb10Zr alloy was modeled by a one-layer circuit. In general, the new TiNbZr alloys showed similar behavior to that observed for the Ti6Al4V. XPS results suggest, in the case of the TiNbZr alloys, the presence of a thicker passive layer containing a lower fraction of TiO2 phase than that of Ti6Al4V. After long-term immersion, all alloys develop a calcium phosphate phase on the surface. The new TiNbZr alloys appear as potential candidates to be used as a substitute to Ti6Al4V in the manufacturing of dental implant-abutment sets.